Comparison of Clinical Performance and Pharyngeal Leak Pressure of Laryngeal Mask Airway Supreme Before and After Cisatracurium (Community Based Medical Journal, 2025)
The laryngeal mask airway (LMA) supreme is a widely used supraglottic airway device that provides effective ventilation with a secure seal. Pharyngeal leak pressure is a critical parameter reflecting airway sealing efficiency. The administration of neuromuscular blockers like cisatracurium may influence the device’s performance, potentially affecting ventilation and airway safety. A prospective, observational study was conducted in the Department of Anaesthesia, Analgesia & ICU at Jaber Al Ahmed Armed Forces Hospital, Kuwait, from January to December of 2021, to compare the clinical performance and pharyngeal leak pressure of the LMA Supreme before and after cisatracurium administration in surgical patients. A total of 120 patients undergoing urologic surgery under general anaesthesia were included in this study, through purposive sampling, based on inclusion and exclusion criteria. They were divided into group A (no muscle relaxant) and group B (Cisatracurium 0.1 mg/kg) having 60 patients in each group. Data on age and gender, duration of surger and anaesthesia, insertion time, attempts, jaw relaxation/stiffness, pharyngeal leak pressure, haemodynamics and complications were recorded and analyzed. Successful insertion within 15 seconds was higher in group B (73.3%) than in group A (66.7%), while prolonged insertion was more frequent in group A (10.0%) than in group B (3.3%); however, the difference was not statistically significant (p>0.05). Patients of group A had significantly lower pharyngeal leak pressure than that of group B (32.1±4.6 cm H₂O vs. 36.2±4.2 cm H₂O; p